Role of catalytic reactions in a flow-induced due to outer stationary and inner stretched coaxial cylinders: An application of Probabilists’ Hermite collocation method - Madhu J; Rania Saadeh; Karthik K; R.S. Varun Kumar; R. Naveen Kumar; R.J. Punith Gowda; Umair Khan; Amal Abdulrahman; M. Modather M. Abdou (Case Studies in Thermal Engineering, 2024)
This paper investigates the impact of homogeneous-heterogeneous chemical reactions on the flow between the coaxial cylinders with heat generation/absorption. From an engineering perspective, in energy absorber design for the shrinking and expanding of a circular metal tube in the production of extruding materials by stretching cylinders designing with great care is necessary to regulate skin friction and heat transfer rate. Studying processes in confined geometries enhances the basic knowledge of chemical kinetics and fluid dynamics. Researchers may increase the chemical processes efficiency/heat transfer activities by designing systems with an optimized flow and analysing the effects of reactions on flow. Both cost reductions and higher-quality products may result from this optimization. This research may yield insights with far-reaching implications across multiple disciplines. The modelled equations are transformed into ordinary differential equations by employing apt similarity transformations and obtained equations are solved using the collocation method with Probabilists’ Hermite polynomial. Graphs illustrating the variation of velocity, thermal, and concentration profiles have been plotted using the influence of various parameters. The increase in curvature parameter causes the velocity and thermal profile upsurge. The rise in heat source/sink parameter improves the heat transport. As the heterogeneous and homogeneous parameters upsurge, the concentration profile decreases.